The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1590/s1516-35982010000900029
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and post-calving forage systems and reproductive performance of primiparous cows

Abstract: -During pre and post calving periods, it was evaluated the influence of the following forage systems on reproductive performance of primiparous cows: natural pasture during pre and post-calving periods; natural pastures during pre-calving period and improved pastures during post-calving period; improved pastures during pre-calving and natural pasture during post-calving; improved pasture during pre-and post-calving periods. The lowest body weights and body condition scores were observed on cows kept on natural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
(35 reference statements)
1
3
0
2
Order By: Relevance
“…Providing the protein-energy supplementation during the pre and postpartum period produces interesting results, which lead to the reduction of the calving interval in up to 27 days. Similar result in a study evaluating the use of improved versus natural pastures was reported (Lobato et al, 2010). By providing better pre and postpartum nutritional level, PREPOST allowed to reach a calving interval shorter than those considered the ideal calving interval (365 days) to obtain one calf/cow/year.…”
Section: Resultssupporting
confidence: 75%
“…Providing the protein-energy supplementation during the pre and postpartum period produces interesting results, which lead to the reduction of the calving interval in up to 27 days. Similar result in a study evaluating the use of improved versus natural pastures was reported (Lobato et al, 2010). By providing better pre and postpartum nutritional level, PREPOST allowed to reach a calving interval shorter than those considered the ideal calving interval (365 days) to obtain one calf/cow/year.…”
Section: Resultssupporting
confidence: 75%
“…However, if this continues throughout the years, heifer frame and weight may increase due to selection of larger animals, which may result in late sexual maturity and higher maintenance requirements of the breeding herd caused by the larger mature size (Jenkins & Willians, 1994;Cundiff et al, 1998), affecting fist-calf cow reproduction, as observed by Olson (1994) and recently by Lobato et al (2010) and Tanure et al (2011). Although all heifers were born in the same season of 90 days in 2006, weight groups may have been confused with age in days, as the precise date of birth of the heifers was no available.…”
Section: Resultsmentioning
confidence: 99%
“…Porém, de nada vale esta prenhez precoce das novilhas se as mesmas não repetirem cria, sendo perdida toda a alimentação diferenciada para acelerar o processo de puberdade e acasalamento (27) , bem como sendo descartados por infertilidade animais geneticamente superiores em rebanhos que trabalham com melhoramento genético (29) . Isso é determinado, provavelmente, pelo maior tempo de recuperação das vacas, com maiores pesos, condições corporais e, consequentemente, melhor resposta reprodutiva (9) .…”
Section: Resultsunclassified
“…A prenhez de primíparas pode ser melhorada, através da utilização de pastagens cultivadas de ciclo hibernal no pós-parto (9) , ajuste de carga animal (7) , utilização de desmame precoce (8) , utilização de suplementação estratégica no pré e pós-parto (6) . Além destes fatos, melhores escores de condição corporal e a idade são fatores a influenciar a prenhez de primíparas (10) .…”
Section: Introductionunclassified